2022
DOI: 10.1002/app.53122
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable poly(butylene succinate‐co‐butylene furandicarboxylate): Effect of butylene furandicarboxylate unit on thermal, mechanical, and ultraviolet shielding properties, and biodegradability

Abstract: Biobased co-polyesters poly(butylene succinate-co-butylene furandicarboxylate) (PBSF) is prepared by transesterification and polycondensation of dimethyl succinate (DSMu), dimethyl 2,5-furandicarboxylate (MDFD) and 1,4-butanediol (1,4-BDO). GPC analysis shows that PBSF has high molecular weight with weight average molecular weight (M w ) up to 11 Â 10 4 g/mol. Due to the low -COOH content, PBSF also has excellent thermal stability, which is beneficial to the polyester processing. Differential scanning calorime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…These results indicated the existence of a repeating unit of PBS in the copolymers . It could be seen from Figure (1) that the bands around 1050, 1310, and 870 cm –1 correspond to Si–O–Si stretching vibration, C–H of the Si-CH 3 stretching vibration, and bending vibration, respectively . As shown in Figure (3), the absorption band of the C–H bending vibration was fitted by peak splitting, and the C–H bending vibration absorption peak on repeating units of PDMS could be found at 1045 cm –1 .…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…These results indicated the existence of a repeating unit of PBS in the copolymers . It could be seen from Figure (1) that the bands around 1050, 1310, and 870 cm –1 correspond to Si–O–Si stretching vibration, C–H of the Si-CH 3 stretching vibration, and bending vibration, respectively . As shown in Figure (3), the absorption band of the C–H bending vibration was fitted by peak splitting, and the C–H bending vibration absorption peak on repeating units of PDMS could be found at 1045 cm –1 .…”
Section: Resultsmentioning
confidence: 68%
“…The disappearance of protons on methyl in DMS at 3.95 ppm indicated that DMS completely reacted and formed covalent bonds in the macromolecular chain of the copolymers. The peaks appearing at 1.7 and 4.1 ppm were attributed to the H of the methylene on the BDO residual in the macromolecular structure, and the peak of the DMS residual in the macromolecular structure was observed at 2.7 ppm . The 1 H-signal on the PDMS appeared at around 0.1 ppm .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations